Computational Analysis of Hyperthermia Therapy on Breast Tumors - Roseman, Nur Amani Hanis; Kamarudin, Mohamad Saddam; Taib, Ishkrizat`; Tajul Arifin, Ahmad Mubarak; Abd Majid, Abdul Rahman; Khan, Aslam Khan Abdul Azim; Takahisa Yamamoto,; Mohd Nizam Mazlan,; Awaludin Martin, (International Journal of Integrated Engineering, 2026)
Hyperthermia therapy is a beneficial complementary approach in cancer management, facilitating the elevation of tumor tissue temperature to optimize the efficacy of chemotherapy or radiotherapy. The research aims to investigate the influence of tumor volume and quantity on its thermal behavior during hyperthermia, using Computational Fluid Dynamics (CFD) simulation. Simplified spherical breasts and tumors models were utilized to isolate the effects of tumor size and configuration. It encompassed of both single and triple tumors with diameters of 2 cm and 4 cm. The CFD simulation employed ANSYS Fluent and incorporated governing equations including continuity, Navier-Stokes, energy and Pennes bioheat equation to model fluid and heat transfer through biological tissue. The findings show that tumor size significantly affects thermal behavior during hyperthermia. Smaller tumors (2 cm) reach peak temperature of 48-58 °C with an average heating rates of 3.45 to 5.39 °C/cm and the steepest gradients is up to 16.15 °C/cm. This exhibit a more consistent and higher temperature across the tumor volume due to rapid heating and lower thermal mass. In contrast, larger tumor (4 cm) achieve a slightly higher peak temperature of 49-59°C but with  a slower average heating rates of 2.14 to 2.42 °C/cm. These large tumors developed a much wider and persistent high temperatures regions but with a slower temperature decay toward surrounding healthy breast tissues which indicates greater heat retention and thermal inertia. In the configuration of triple 2 cm tumors, the thermal zones overlapped at higher surface temperatures whereas the triple 4 cm tumors produce largely separated thermal regions. These demonstrate that the large tumors volume lead to a reduction in heat overlap and an uneven thermal fields.  Overall, the results demonstrated that both tumor size and configuration significantly influence heat distribution. The CFD modelling proved to be a dependable, non-invasive technique to improve hyperthermia treatment planning for even heating and precise tumor targeting.